Is using combined tillage implements the solution? - Hamid, Ahmed (University of Thi-Qar Journal of agricultural research, 2024)
The fuel consumption, The energy requirement, the time of prepare seedbed, the tractor wheel slippage and the number of passes in the field, all of this factors make farmer choose more efficient method of plowing. Compound tillage is the solve and the method means that two, three or more different plowing tools are work at one time for plowing soil, pulverization, seeding and fertilize, the aid of this way, reduce the drudgery, number and saving time of the field operation. The primary (conventional) and secondary tillage implements are becoming expensive time, fuel and cost, additional, need several passes to prepare seedbed, which increase compaction and damage of the soil and leads to formation the hard pan in the soil due to tractor and machines movement. The farmer size of the field holdings in Iraq is middle or usually small, the way of increase the the width of tools or speed is less useful and effective, therefore, reduce and shorten the number of traffic or passes by use a combination tillage implements consider better solution. Compound tillage saving cost of 44-55%, time of 50-55% and enable the farmers to reduce the number of trips over the field, also, shortage of farm labor. Carrying out the tillage process by compound tillage with two or more equipment to reduce time, fuel consumption and power requirement foe prepare the best seedbed. In this review, various paper researches on combination tillage implement will be discussion.